2003
DOI: 10.1148/radiol.2272011747
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Predictors of Lymph Node Status in Rectal Cancer with Use of High-Spatial-Resolution MR Imaging with Histopathologic Comparison

Abstract: Prediction of nodal involvement in rectal cancer with MR imaging is improved by using the border contour and signal intensity characteristics of lymph nodes instead of size criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
430
1
11

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 757 publications
(469 citation statements)
references
References 21 publications
14
430
1
11
Order By: Relevance
“…At DRE the tumors are found clinically tethered or fixed in 78.4% of the cases. As neither TRUS nor CT could -at that time-provide sufficiently reliable information on clinical N-stage (cN), this variable is not analyzed [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…At DRE the tumors are found clinically tethered or fixed in 78.4% of the cases. As neither TRUS nor CT could -at that time-provide sufficiently reliable information on clinical N-stage (cN), this variable is not analyzed [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, retrospective data have suggested that a combined modality therapy could represent an overtreatment in patients at low risk of local failure after TME alone, such as some tumours staged as T3N0 (Willett et al, 1999). In this setting, MRI plays a key role, because it can predict the CRM involvement (Beets-Tan et al, 2000), so defining the patients at higher risk of local recurrence when treated with TME plus RT (Marijnen et al, 2003), although it has been demonstrated less sensitive and specific at identifying nodal disease and vascular invasion (Brown et al, 2003;Branagan et al, 2004). Our phase I -II study was carried out in patients with LARC at high risk of recurrence, as identified by both EUS and MRI.…”
Section: Discussionmentioning
confidence: 99%
“…However, a limitation remains in differentiating metastatic nodes from normal lymph nodes on the basis of size alone (33). The lymph node shape, signal intensity characteristics, and enhancement pattern may be used to identify lymph node involvement with tumor (34). However, these results are preliminary and require further investigation.…”
Section: Discussionmentioning
confidence: 99%